BIOLOGICAL FERTILIZER EFFECT OF HEAVY METAL ABSORPTION OF COPPER AND LEAD TO BABY CORN CROP - sudaryono, Sudaryono (BPPT)
Absorption of heavy metals by plants is influenced by soil and plant biology. Heavy metals are absorbed into plant tissues through the root, then enter the food chain cycle. Metal will accumulate in body tissues and can have negative impacts for humans, animals, and plants when exceeding the limit of tolerance. Heavy metal accumulation in plant tissues can directly affect plant growth and production, can indirectly affect human health when consuming food contaminated heavy metals. The research objective was to determine the ability of biological fertilizers containing bacteria Azotobacter sp. and Pseudomonas sp., in absorbing heavy metals (Cu and Pb) contained in landfill waste compost, which is used to fertilize crops corn (baby corn). The research methodologyuses a split plot design arranged in Completely Randomized Design with 3 blocks as replicates. The first factor that serves as the main plot of the biological fertilizer, consisting of two cedars, namely: no biological fertilizers and biological fertilizers. The second factor that functions as a sub plot that is a combination of landfill waste compost with NPK fertilizer, consisting of four treatments, namely: Compost waste landfill: no fertilizer NPK = 1: 0; compost waste landfill: NPK = 2/3 : 1/3; compost waste landfill: fertilizer NPK = 1/3: 2/3Without landfill waste compost: NPK = 0: 1. The results showed that administration of biological fertilizers in combination with compost waste landfill is more dominant for increasing and improving soil physical chemistry, such as increasing soil pH, nutrients nitrogen, phosphorus and potassium and cation exchange capacity (KPK). Biological fertilizer containing bacteria Azotobacter sp. and Pseudomonas sp. may reduce the uptake of heavy metals Cu to below the threshold of 2.526 to 15.79 ppm, the maximum content of Cu ranges between 20-100 ppm. The mean content of Pb in tissues and cobs of corn is above the maximum limit of 29.80 to 42.69 ppm, which is still allowed Pb content between 0.1 to 10 ppm. Means baby corn crop is not safe for consumption.key words: compost from the landfill, heavy metals, biological fertilizer